2023
DOI: 10.1002/adfm.202214562
|View full text |Cite
|
Sign up to set email alerts
|

Undoped Hole Transport Layer Toward Efficient and Stable Inorganic Perovskite Solar Cells

Abstract: Numerous strategies have been practiced to improve the power conversion efficiency of CsPbI 2 Br-based perovskite solar cells (PSCs), which definitely makes efficiency gradually approach the theoretical efficiency limit. However, sufficient device stability is still in urgent demand for commercialization, pushing to overcome some instability sources induced by hygroscopicity of spiro-OMeTAD and residual strain of perovskite layer. To address these issues, p-type semiconductor of PCPDTBT is used to replace spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The results clearly showed that the addition of TPA─O and TPA─Cl accelerated the hole extraction from perovskite toward the HTL, but the hole extraction was clearly inhibited in the case of TPA-CN, as evidenced by steady-state PL results (Figure 4E). [31] This was further confirmed by a long PL lifetime (452.43 ns) for TPA-CN compared to the control (444.75 ns) and TPA─O (245.60 ns) (Figure 4F and Table S1, Supporting Information). The variation in the hole extraction ability for three molecules may result from their different electronegativity and molecular geometry at the interfaces, as similarly discussed by AMID.…”
Section: Resultssupporting
confidence: 57%
“…The results clearly showed that the addition of TPA─O and TPA─Cl accelerated the hole extraction from perovskite toward the HTL, but the hole extraction was clearly inhibited in the case of TPA-CN, as evidenced by steady-state PL results (Figure 4E). [31] This was further confirmed by a long PL lifetime (452.43 ns) for TPA-CN compared to the control (444.75 ns) and TPA─O (245.60 ns) (Figure 4F and Table S1, Supporting Information). The variation in the hole extraction ability for three molecules may result from their different electronegativity and molecular geometry at the interfaces, as similarly discussed by AMID.…”
Section: Resultssupporting
confidence: 57%
“…These PVKs have high PCEs of 21.59%, 17.7%, 15.54%, and 11.08%, respectively, in the n-i-p structure in addition to other advantages and drawbacks [31][32][33][34][35]. However, all-inorganic PVKs have low PCE, which can be addressed using different approaches such as by optimizing their structure via different methods such as additive-assisted airflow drying method [36], adding passivators such as surface passivation agents and bulk passivators [37], optimizing the composition of the carrier transport layer [38], adding different layer structures [39], fabricating PVK-PVK stacks [40], and optimizing the ratio between alloy PVK atoms. These methods have effectively improved the photoelectric conversion efficiency of PSCs; however, they have not yet reached the Shockley-Queisser (S-Q) limit of 33.7%.…”
Section: Inorganic Pscsmentioning
confidence: 99%
“…[ 111 ] To address this concern, a transport layer with a TEC larger than that of the perovskite can be used to compensate for tensile strain during thermal annealing. [ 112 ] The polystyrene with low glass transition temperature was deposited onto the tin oxide layer as a buffer layer for stress compensation of FA 0.75 MA 0.25 Pb(I 11/12 Br 1/12 ) 3 thin film, as shown in Figure 7c. [ 113 ] Subsequently, Chen and co‐workers reported an ultrathin Eu‐metal–organic frameworks (MOFs) layer at the interface between the transport layer and perovskite services as an ultraviolet filter to protect the solar cell, as shown in Figure 7d.…”
Section: Strategies To Mitigate Adverse Effectsmentioning
confidence: 99%